Late-Holocene environmental variability at Munsa archaeological site, Uganda: a multicore, multiproxy approach - Lejju, B.J.; Taylor, D.; Robertshaw, P. (The Holocene, 2005)
Palaeoenvironmental data, in the form of 113 counts of pollen, fungal spores and charcoal abundances, 121 counts of phytoliths and 15 AMS 14C dates (11 macrofossil and 4 bulk sediment samples), have provided a means of reconstructing the late-Holocene environmental history of Munsa archaeological site, Uganda. The data were extracted from sediment cores from what is today a papyrus swamp, located within an area described by an outermost ring of earthworks at Munsa. Sediment core data indicate the general presence of forested conditions to C. AD 1 100, although there is evidence for the local presence of food plants prior to this date. Deforestation from c. AD 1100 is marked in both the pollen and phytolith records, while fungal spores indicate the presence of increased numbers of herbivores post-deforestation. Indicators of deforestation and increased herbivore numbers broadly accord with the archaeological evidence for substantial occupation of the site at Munsa and the establishment of a mixed economy based on crops, cattle and iron working. Evidence for forest recovery and reduced herbivore numbers locally from C. AD 1780 could reflect abandonment of permanent settlement at the site, possibly during or following a period of drought and/or political upheaval in the region. Fungal spores and phytoliths provide evidence of agricultural activities at Munsa that have not left an imprint on pollen records, thus supporting the case for the use of multiproxies in palaeoenvironmental research, while intercore differences between the three sediment cores analysed, although relatively minor, confirm the benefits of a multicore approach. Tentative evidence for the very early presence of Musa (cultivated edible banana) is provided and warrants further study.
Keywords: Africa; Uganda; Archaeology; Environmental variability; Banana cultivation; Charcoal; Climate change; Fire; Fungal spores; Pollen; Phytoliths; Late Holocene.